Brazil and the nonproliferation regime: a historical perspective. Issue 5 (1st November 2016) - de Queiroz Duarte, Sergio
ABSTRACT: This article addresses the historical relations between Brazil and the international nonproliferation regime. It also discusses the current position of the Brazilian government regarding the Additional Protocol and the Treaty on the Non-Proliferation of Nuclear Weapons, as well as some aspects of the Brazilian nuclear program.